A history of vacuum technology from 5th Century BC and a personal view of progress in the field, including medical applications, from 1959 to 2021. (April 2022) - Colligon, John S.
Abstract: This article looks at the development of vacuum from its known origins in 500 BC to an important field of modern science with numerous applications in industry and, more recently, in medicine. The author describes his personal experience in vacuum research and vacuum community activity. The main achievements of his team and colleagues are highlighted in this paper.